Role of Interventional Radiology in the Emergent Management of Acute Upper Gastrointestinal Bleeding - Navuluri, Rakesh; Patel, Jay; Kang, Lisa (Seminars in Interventional Radiology, 2012)
Approximately 100,000 cases of upper gastrointestinal bleeding (UGIB) require inpatient admission annually in the United States. When medical management and endoscopic therapy are inadequate, endovascular intervention can be lifesaving. These emergent situations highlight the importance of immediate competence of the interventional radiologist in the preangiographic evaluation as well as the endovascular treatment of UGIB. We describe a case of UGIB managed with endovascular embolization and detail the angiographic techniques used. The case description is followed by a detailed discussion of the treatment approach to UGIB, with attention to both nonvariceal and variceal algorithms.
Keywords: embolization; upper gastrointestinal hemorrhage; emergent; TIPS